2021
DOI: 10.12968/hmed.2020.0571
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning for patients with COVID-19: a communication guide

Abstract: In view of the high morbidity and mortality associated with COVID-19, early and honest conversations with patients about goals of care are vital. Advance care planning in its traditional manner may be difficult to achieve given the unpredictability of the disease trajectory. Despite this, it is crucial that patients' care wishes are explored as this will help prevent inappropriate admissions to hospital and to critical care, improve symptom control and advocate for patient choice. This article provides practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“… 10 - 13 In the setting of the COVID-19 pandemic, there have been multiple interventions developed, such as communication guides, 14 - 16 new workflows 17 and COVID-19 goals of care videos, 18 to help providers conduct ACP discussions in the context of COVID-19 infection. 19 - 23 However, despite the overwhelming consensus on their necessary roles during the COVID-19 pandemic, the rates of ACP for patients admitted for COVID-19 remains understudied. 6 , 8 , 24 - 26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 - 13 In the setting of the COVID-19 pandemic, there have been multiple interventions developed, such as communication guides, 14 - 16 new workflows 17 and COVID-19 goals of care videos, 18 to help providers conduct ACP discussions in the context of COVID-19 infection. 19 - 23 However, despite the overwhelming consensus on their necessary roles during the COVID-19 pandemic, the rates of ACP for patients admitted for COVID-19 remains understudied. 6 , 8 , 24 - 26 …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] In the setting of the COVID-19 pandemic, there have been multiple interventions developed, such as communication guides, [14][15][16] new workflows 17 and COVID-19 goals of care videos, 18 to help providers conduct ACP discussions in the context of COVID-19 infection. [19][20][21][22][23] However, despite the overwhelming consensus on their necessary roles during the COVID-19 pandemic, the rates of ACP for patients admitted for COVID-19 remains understudied. 6,8,[24][25][26] In the setting of the acute risk for death, rapid deterioration, and poor outcomes related to COVID-19, ACP has become more important than ever in patients admitted to the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment escalation decisions have historically been different from DNACPR orders 25. It has been suggested that both processes can be combined by putting cardiopulmonary resuscitation decisions in the context of overall goals of care, that is, what treatments or outcomes a patient expects, accepts and wants 26.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment escalation decisions have historically been different from DNACPR orders. 25 It has been suggested that both processes can be combined by putting cardiopulmonary resuscitation decisions in the context of overall goals of care, that is, what treatments or outcomes a patient expects, accepts and wants. 26 Our results demonstrate that DNACPR decisions were closely linked to escalation status during the first pandemic wave, but also later in the pandemic, with nearly 95% of patients who were deemed unsuitable for critical care admission receiving DNACPR orders during or immediately after review by critical care specialists.…”
Section: Dnacpr Orders and Escalation Statusmentioning
confidence: 99%
“…Conversations conducted over the phone or via video conference are unique in that individuals lose non-verbal cues on both sides of the conversation. 1 Communication guides 35 have suggested verbally acknowledging emotion to convey compassion as a core skill in conducting GOC conversations over the phone. 36 Lastly, the ability to have effective conversations in a time of clinical urgency is important in the setting of any rapidly deteriorating patient.…”
Section: Discussionmentioning
confidence: 99%